The influence of board director's characteristics and ownership structure on intellectual capital disclosure among Gulf Cooperation Council companies - Qeshta, Mohammed H.M (2015)
Intellectual capital (IC) disclosure, recognised as a highly useful element for maintaining competitive advantage, attracting global investment and adding immense value to the interests of key stakeholders has been presented as an international research direction, especially in the Gulf Co-operation Council (GCC) context. As such, this study addresses the key issue of examining voluntary disclosure of IC among top listed firms in the GCC countries. Specifically, it involves a thorough examination of 119 firms’ 2011 annual reports. Furthermore, it investigates whether the monitoring mechanisms of an effective board and audit committee, and ownership structures, influence IC disclosure. By using hierarchical regression, this study also estimates the moderating effect of the effectiveness of audit committees on the relationship between ownership (e.g. government, family, institutional) and IC disclosure. The multiple regression findings showed that the board size, board multiple directorships, board meeting, board committees and audit committee independence had a positive and significant relationship with IC disclosure when examined individually. However, when assessed at aggregate level using scores, it was found that the board effectiveness and family ownership had a significant relationship with IC disclosure in the GCC context. Additionally, this study provides evidence related to family and institutional ownership holding a majority of shares having a significant relationship with IC disclosure. Also, the results of this study showed that audit committee effectiveness moderates the relationship between the government ownership and IC disclosure. The result of this study contributes to the body of knowledge in IC-related studies, particularly with regards to monitoring mechanisms affecting IC disclosure. The findings will be beneficial to investors, regulators, policymakers and market participants as well as researchers.